2020
DOI: 10.1177/0269881119897556
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid receptor type 1 in the bed nucleus of the stria terminalis modulates cardiovascular responses to stress via local N-methyl-D-aspartate receptor/neuronal nitric oxide synthase/soluble guanylate cyclase/protein kinase G signaling

Abstract: Background: Endocannabinoid neurotransmission in the bed nucleus of the stria terminalis is involved in the control of cardiovascular responses to stress. However, the local mechanisms involved is this regulation are not known. Aims: The purpose of this study was to assess an interaction of bed nucleus of the stria terminalis endocannabinoid neurotransmission with local nitrergic signaling, as well as to investigate the involvement of local N-methyl-D-aspartate glutamate receptor and nitric oxide signaling in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 57 publications
(126 reference statements)
1
12
0
Order By: Relevance
“…As stated in the Introduction, previous studies provided evidence of GABAergic inputs within the LH arising from the BNST 33 , 34 . These neuroanatomical evidence, taken together with results mentioned above that CB 1 receptor activation during aversive threats acts mainly inhibiting glutamatergic terminals during aversive threats 16 , 17 , 35 indicate that the decrease in number of Fos-immunoreactive cells in the LH observed in the present study in animals treated with the CB 1 receptor antagonist in the BNST might be the resulted of an increased local glutamatergic neurotransmission, which in turn increase activation of BNST GABAergic neurons projecting to the LH. The hypothesis that GABAergic connection with the LH mediates the inhibitory control of BNST CB 1 receptor was further supported by demonstration that LH pretreatment with the GABA A receptor antagonist SR95531 completely inhibited the facilitation of HR increase to restraint stress caused by BNST treatment with the CB 1 receptor antagonist AM251.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…As stated in the Introduction, previous studies provided evidence of GABAergic inputs within the LH arising from the BNST 33 , 34 . These neuroanatomical evidence, taken together with results mentioned above that CB 1 receptor activation during aversive threats acts mainly inhibiting glutamatergic terminals during aversive threats 16 , 17 , 35 indicate that the decrease in number of Fos-immunoreactive cells in the LH observed in the present study in animals treated with the CB 1 receptor antagonist in the BNST might be the resulted of an increased local glutamatergic neurotransmission, which in turn increase activation of BNST GABAergic neurons projecting to the LH. The hypothesis that GABAergic connection with the LH mediates the inhibitory control of BNST CB 1 receptor was further supported by demonstration that LH pretreatment with the GABA A receptor antagonist SR95531 completely inhibited the facilitation of HR increase to restraint stress caused by BNST treatment with the CB 1 receptor antagonist AM251.…”
Section: Discussionsupporting
confidence: 84%
“…For instance, previous findings identified that CB 1 receptor blockade enhanced stress-evoked c-fos mRNA in the BNST 16 , 17 . Besides, we reported recently that the facilitated tachycardia to restraint stress following BNST treatment with AM251 was inhibited by local NMDA glutamate receptor antagonism within the BNST 35 . The idea that control of cardiovascular responses to restraint by BNST CB 1 receptor is mediated by interaction with local glutamatergic neurotransmission is further supported by evidence that BNST NMDA glutamate receptor plays a facilitatory influence in restraint-evoked HR response without affecting pressor and tail skin temperature changes 39 , 40 .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The animals were kept under a 12-h/12-h light/dark cycle (lights on between 7:00 AM and 7:00 PM) and had free access to water and standard rat food. We chose all group size of all experiments shown in the present study based on previously reported data which are comparable with our experiments (Barretto-de-Souza, Benini, Reis-Silva, & Crestani, 2021;Gomes-de-Souza, Costa-Ferreira, Oliveira, Benini, & Crestani, 2020).…”
Section: Animalsmentioning
confidence: 74%